The Role of Spatial Imagination in the Step-By-Step Description of the Solving of Multiple Problems in Drawing - Galimova, Sh. H. (International Journal on Human-Computing Studies, 2023)
In this article, it is described how to show graphic operations in solving problems related to sections of polynomials, to develop students' spatial imagination.